Enhancing Fracture and Wear Resistance of Dentures/Overdentures Utilizing Digital Technology: A Case Series Report. Issue 6 (24th February 2016) - Afify, Ahmed; Haney, Stephan
Abstract: Since it was first introduced into the dental world, computer‐aided design/computer‐aided manufacturing (CAD/CAM) technology has improved dramatically in regards to both data acquisition and fabrication abilities. CAD/CAM is capable of providing well‐fitting intra‐ and extraoral prostheses when sound guidelines are followed. As CAD/CAM technology encompasses both surgical and prosthetic dental applications as well as fixed and removable aspects, it could improve the average quality of dental prostheses compared with the results obtained by conventional manufacturing methods. The purpose of this article is to provide an introduction into the methods in which this technology may be used to enhance the wear and fracture resistance of dentures and overdentures. This article will also showcase two clinical reports in which CAD/CAM technology has been implemented.